Integrated healthcare monitoring device for obese adults using internet of things (IoT) - Dev Gupta; Akanksha Parikh; R. Swarnalatha (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Obesity is a global epidemic, often considered an impending disaster for the world’s population. Healthcare organizations and professionals repeatedly emphasize the negative impacts on obesity in the development of cardiovascular diseases, hypertension and diabetes. The continuous monitoring of physiological parameters; namely SpO2, blood pressure, body temperature and pulse rate are imperative for obese adult patients. IoT is a dynamic field, used extensively in all fields: agriculture, automobile, manufacturing and retail industry primarily for automated remote real-time monitoring. This paper focuses on the implementation of IoT in the healthcare industry for monitoring and evaluating health conditions of obese adults, along with emphasis on the importance of medical data storage. Furthermore, a device is developed with a novel design and system, which not only allows real-time monitoring but also the storage of medical records for multiple patients simultaneously. The device facilitates measurements of these parameters using an Arduino environment and then transmits the data onto an IoT dashboard using a Wi-fi module for remote monitoring for healthcare professionals. The main aim is to provide a suitable device recommended by doctors for patients suffering from obesity, such that doctors can examine patient’s health trends over a period from the stored data for monitoring any changes that could be a symptom of an underlying unnoticed health condition.